MicroRNA-27a controls the intracellular survival of Mycobacterium tuberculosis by regulating calcium-associated autophagy - Feng Liu; Jianxia Chen; Peng Wang; Haohao Li; Yilong Zhou; Haipeng Liu; Zhonghua Liu; Ruijuan Zheng; Lin Wang; Hua Yang; Zhenling Cui; Fei Wang; et al. (Nature Communications, 2018)
How Mycobacterium tuberculosis (Mtb) escapes autophagy-mediated clearance is poorly understood. Here, Liu et al. show that Mtb-induced MicroRNA-27a targets the ER-associated calcium transporter CACNA2D3, leading to suppression of antimicrobial autophagy and to enhanced intracellular survival of Mtb.